2011
DOI: 10.1115/1.4005167
|View full text |Cite
|
Sign up to set email alerts
|

Near Valve Flows and Potential Blood Damage During Closure of a Bileaflet Mechanical Heart Valve

Abstract: Blood damage and thrombosis are major complications that are commonly seen in patients with implanted mechanical heart valves. For this in vitro study, we isolated the closing phase of a bileaflet mechanical heart valve to study near valve fluid velocities and stresses. By manipulating the valve housing, we gained optical access to a previously inaccessible region of the flow. Laser Doppler velocimetry and particle image velocimetry were used to characterize the flow regime and help to identify the key design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…This is particularly important when considering mechanical valves. Our study demonstrated superior optimization potential when using mechanical valves, but it did not show the increased blood damage potential during leaflet closure reported by other studies (35,36). This limited scope of modeling would thus artificially favor mechanical valves over biological ones.…”
Section: Abnormal Aortic Flow Is Usually Characterized By Several Factorscontrasting
confidence: 65%
“…This is particularly important when considering mechanical valves. Our study demonstrated superior optimization potential when using mechanical valves, but it did not show the increased blood damage potential during leaflet closure reported by other studies (35,36). This limited scope of modeling would thus artificially favor mechanical valves over biological ones.…”
Section: Abnormal Aortic Flow Is Usually Characterized By Several Factorscontrasting
confidence: 65%
“…When the blood flow passes through the MHV, it will generate a high-pressure drop, resulting in recirculation and stagnation [ 67 70 ]. The increase of shear stress will lead to blood damage (hemolysis) and platelet activation.…”
Section: Simulation Of Physical Quantity Dysfunctionmentioning
confidence: 99%
“…Although the shear rate is generally high in large arteries, some cardiovascular disease induces blood flow disturbance and generates stagnant and recirculation regions, significantly reducing the shear rate [ 133 ]. When the blood flows through the MHV, the recirculation, stagnation, vortex structures, and flow separation are obvious, which enhance the probability of occurrence of low shear rates and require the use of the non-Newtonian models [ 21 , 26 , 35 , 67 70 ]. In dysfunction MHV simulation, the blood flow behind the dysfunction leaflet has more significant recirculation flow and stagnation.…”
Section: Non-newtonian Blood Flowmentioning
confidence: 99%
“…These complications are thought to be due to nonphysiologic shear stress levels imposed on blood elements by complex flows through BMHVs [6][7][8]. Thrombus formation in the valves may lead to dislodged emboli that can cause stroke and death [9][10][11], Various experimental studies have been performed on flow through prosthetic heart valves to study the complex flow dynamics [12][13][14][15][16], though experimental studies are often limited to lower spatiotemporal resolution and obstructed viewpoints. Blood damage experiments are also possible, in which human blood can be run through valves and assays are performed to assess blood damage potential [17][18][19], but only give bulk blood damage results.…”
Section: Introductionmentioning
confidence: 99%